COGNITIVE MODELING OF SYNONYMIC PARADIGMS AND THEIR TEXT-FORMING POTENTIAL IN DIGITAL ENVIRONMENTS - Latifa Shirzadova (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article examines the cognitive modeling of synonymic paradigms and their role in text formation within digital communication environments. It is grounded in cognitive linguistics, discourse analysis, and computational linguistics, combining theoretical and applied perspectives to explain how synonymy functions beyond simple lexical equivalence. The main focus is on understanding synonymic paradigms as dynamic cognitive structures that reflect conceptual organization in the human mind and simultaneously operate as computational resources in modern language technologies. The study begins by outlining the cognitive foundations of synonymy, emphasizing that lexical meaning is usage-based and context-dependent rather than fixed. Drawing on works by Lakoff, Croft and Cruse, and Evans and Green, it explains that synonymic relations are best understood as networks of near-synonymous expressions organized around shared conceptual domains. These networks are shaped by Idealized Cognitive Models and manifested through graded semantic similarity rather than absolute identity. The article further explores the transformation of synonymy in digital environments, where computational models such as word embeddings and transformer-based neural networks encode synonymic relations as statistical proximity in semantic space. This shift demonstrates how cognitive linguistic principles align with modern natural language processing systems in representing meaning through usage patterns and contextual similarity. A significant part of the study is devoted to the text-forming potential of synonymic paradigms. It highlights their role in lexical cohesion, stylistic variation, and discourse framing. Synonymic choice is shown to influence tone, ideological positioning, and pragmatic interpretation of texts, particularly in digital communication where algorithmic systems also shape lexical selection. In conclusion, the article argues that synonymic paradigms function as an intersection between cognition, discourse, and computation. They are essential both for human meaning-making and for machine-based language processing. This dual nature positions synonymy as a central mechanism in understanding modern text production in digitally mediated environments.